The Correlation of Teacher Management, Characteristics, and Regulatory Conformity with the Effectiveness of Integrated Islamic Elementary Schools in Riau Islands Province - Sulikah; Risnita; M.Syahran Jailani (Maneggio, 2026)
This study aims to test the hypothesis correlation of teacher management, characteristics, and regulatory conformity with the effectiveness of integrated Islamic elementary schools in Riau Islands Province. This research employs a quantitative approach with a survey method. The sampling technique used a probability sampling technique with a sample of 100 teachers of integrated Islamic schools in Riau Islands Province. Hypothesis testing used correlation analysis with a significance level ɑ = 0.05. The data of the results of this study concluded that both partially and simultaneously there were: 1). the direct relationship between teacher management (X1) and the effectiveness of primary schools (Y) with a correlation coefficient value of rx1y = 0.78 and the contribution of teacher management scores to primary school effectiveness obtained a value of 60.84%. 2) the direct relationship between characteristics (X2) with the effectiveness of primary school (Y) with the value of the correlation coefficient of rx2y = 0.77 and the Contribution of the Value between the characteristics and the effectiveness of the primary school obtained a value of 59.29%, 3) the direct relationship between the conformity of regulations (X3) and the effectiveness of the primary school (Y) with the value of the correlation coefficient rx3y = 0.80 and the contribution of the value between the conformity of regulations and the effectiveness of primary schools was obtained with a score of 64%, 4) a simultaneous direct relationship between teacher management (X1), characteristics (X2), and regulatory conformity (X3) with primary school effectiveness (Y), with a calculated F value of 366.67 and a table F of 3.10 with a correlation coefficient (Rx1x2x3Y) of 0.88. The implication of this study is that based on the results of the analysis, it is known that Teacher Management, Characteristics, and Regulatory Conformity simultaneously have a significant correlation with School Effectiveness. This means that the effectiveness of schools is not determined by a single factor, but is the result of synergy between leadership and teacher management, the characteristics of the education system, and supporting regulations. These three factors form a unified system that strengthens each other in improving the quality of education.